Study of fatigue characteristics of key welds of modular drilling derricks - zhang, zhe; Tian , Jialin; Liu, Chenghang; Xiong, Changqing (CT&F - Ciencia, Tecnología y Futuro, 2023)
Driven by the gradual development of oil and natural gas resources, the global use of rigs and the number of wells rise steadily. Modular rigs play an important role in oil exploration because of their efficient transport, economy, technological advancement, and rig reliability. The derrick is a key part of the modular rig, and since many essential components in the derrick are welded, the fatigue life of the derrick weld is particularly relevant. In this paper, the modular rig is the object of the research, proposing the calculation formula of fatigue life of the key weld of the derrick. Using modular rig ZJ90D as an example, and combining the rig working conditions with the structural characteristics of the derrick, the key calculation parameters are obtained by numerical analysis. Thus, the life expectancy of the key weld is calculated according to the calculation formula of fatigue life presented herein. The research results have important reference significance and guiding value for the design and optimization of modular rig derricks.